A Case Study of Deep Shaft and Open Face Tunnelling Induced Excessive Ground Settlement in Water Rich Strata in Guangzhou, China - Nong, Xingzhong; Liang, Yuehua; Ruan, Yanmei (Frontiers in Earth Science, 2022)
During a shaft and associated sprayed concrete lining (SCL) tunnel construction in a new line of Guangzhou Metro, site monitoring recorded ground surface settlements was much larger than that predicted in the design. This raised the alarm to the safety of an adjacent high pressure gas pipe. Close-form and analytical equations calculation and non-coupled and coupled numerical analyses were carried out to back analysed the settlement. It was found the primary contributing factor to the excessive ground settlement is the water loss induced ground consolidation, which is commonly encountered during underground construction in south China where complex strata, such as granite residual soil and fully weathered granite, present. This paper details the back analysis process and discusses mitigation measures that should be adopted for construction in similar ground in the future.